Adolescents and coaches/trainers perspectives of ergogenic sports supplement use within South African private high schools - Butler, Nicholas John (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Sports supplements, also referred to as ergogenic aids, are used because of the assertion that they can enhance physical or athletic performance and/or physical appearance. Commonly used sports supplements include creatines, proteins, amino acids, stimulants, and in some cases pro-hormones. There is a relatively high and increasing prevalence of sports supplement use by the general population globally and in South Africa, particularly among adolescents and young adults due to various factors. While some research has explored supplement use among adolescents in a school setting, no study has explored this across the private school system in South Africa. Additionally, given the important role that coaches/trainers play in adolescent development, it is critical to also understand the role that they play regarding adolescent supplement use, given that there has been limited research around this topic in South Africa. Therefore, there were two aims of this study; Firstly, this study explored the prevalence and perceptions (knowledge; attitudes; beliefs) of sports supplements among South African private high school adolescents. Secondly, this study explored the perceptions (knowledge; attitudes; application of knowledge) towards sports supplements among adolescent coaches/trainers in South African private high schools. Considering the dual aim of this study, this thesis was structured as a two-part research study. Both parts took the form of a cross-sectional design, using an online questionnaire to collect qualitative and quantitative data. In total, a cohort of n=50 adolescents and n=49 coaches/trainers participated. Adolescent participants reported a high prevalence of sports supplement use (62%) with their main reasons for using them being recovery and performance. Adolescents were primarily influenced/advised by friends and coaches/trainers to start using sports supplements. Coaches/trainers primarily relied on other coaches/trainers and internet advertising/sites as a main source of information. Less than half of the participants from both groups reported having any formal education or training related to sports nutrition or sports supplements. Both groups thought that these products are being misused by adolescents, which may account for why a portion of the adolescent participants reported experiencing adverse side-effects from using sports supplements, and a few coach/trainer participants reported witnessing this in their practice. This may be a result of the professionalisation of school sport which places pressure on athletes and their coaches/trainers to perform and may in turn be the reason why some adolescents reported that they would use, and some coaches/trainers reported they would recommend the use of sports supplements even if they were aware of risk/dangers involved. Thus, there is a need for education/training among South African high school adolescents and their coaches/trainers with respect to the use of sports supplements, so that they can make informed decisions from reliable sources of information or advice in order to use these products safely and effectively.
Keywords: Dietary supplements; Energy metabolism; Teenagers -- South Africa; Teenagers Physiology -- South Africa; Teenagers Substance use -- South Africa; Coaches (Athletics) -- South Africa; Athletic trainers -- South Africa; Private schools -- South Africa; Ergogenic aids